Improving Social and Emotional Learning for the Students of “Nicolae Bălcescu” Land Forces Academy of Sibiu during the English Language Classes - Macovei Crenguța Mihaela; Lică Gabriela Mihăilă; Negoescu Alina Gabriela (Scientific Bulletin, 2025)
This paper aims to analyse the influence of certain demographic (gender, year of study, graduated high school and major) and psychological (grit, self-management, and social awareness) characteristics of military students regarding their classroom effort and self-efficacy about English subjects. The results of the independent samples t-test revealed that there were significant differences between male and female students only in terms of classroom effort and self-management. The level of classroom effort of the students in the sample is predicted by the combination of gender, year of study, level of social awareness and grit. The female students put in more effort into activities in English classes; also, students in their third year of study seem to put more effort than their first- and second year peers. The levels of social awareness and grit are associated in determining the level of classroom effort: the higher the level of social awareness, the more effort the cadets put into the activities in English classes and the higher their sense of self-efficacy in solving English tasks.